ANALISA UNJUK KERJA MOTOR INDUKSI 3 PHASA TERHADAP PENGARUH HARMONISA (THD) DENGAN PENAMBAHAN FILTER AKTIF MENGGUNAKAN MATLAB - I Nyoman Duarsana; I Wayan Rinas; I Wayan Arta Wijaya (Program Studi Teknik Elektro UNUD, 2021)
Operating non-linear loads can cause harmonic distortion, one of which is aninduction motor. Harmonics can cause the system power quality content level to become worse.One way to reduce harmonics is with an active filter. Theemethodduseddin thissresearchhisstheSimulink method in Matlab. The addition of an active filter aims toreduceetheeharmonicccontent in thennetwork in order toosee theeeffect ofhharmonics ontttheperformanceeeof the 3 phase induction motor on rotation and torque. The results of simulationanalysis using Matlab show that active filters can reduce the harmonic content in the networkcompared to networks without using active filters. The decrease that occurred in THDI was11.88% in the Rrphase, 11.87% in theeSsphaseaand 11.88% in the Ttphase with a load of 3motors. There is no change in motor performance at rotation and torque, namely the rotation of1498 Rpm and torque of 0.4682 Nm.